Excretion calculations of sheep and goats in Finland - Nousiainen, Jouni; Vattulainen, Jenni; Kuoppala, Kaisa; Rinne, Marketta (Luonnonvarakeskus, 2026)
The official excretion calculations provide the Finnish national annual amounts of dry matter, organic matter and nutrients excreted by different livestock into faeces and urine. Natural Resources Institute Finland (Luke) is responsible for the national excretion calculations in Finland, and the results are used e.g. in estimating emissions during manure management and use into air (greenhouse gases, ammonia) and waters [phosphorus (P), nitrogen (N), potassium (K)], in estimating the quantity and composition of manure produced in Finland and in setting the targets to improve its utilization (nutrient balances, circular economy). The amounts of nutrients excreted are calculated as the difference between nutrient intake in feed and the nutrients retained in the animals as well as in their products, i.e. as "nutrient input – nutrient retained= nutrient excretion" The components included in the calculations are dry matter, organic matter, N, P and K. Excretion calculations of sheep and goats are conducted annually for different animal groups based on their gender and age. The feeds consumed by the animals is one of the most critical aspects of excretion calculations. In this report, the consumption of feeds was evaluated based on energy requirements of animals at different production levels. The composition of diets was based on data gathered from stakeholders and on expert evaluations. The highest uncertainty lies in the actual amount of nutrients consumed by the animals. The detailed steps of calculations are described in this report. Based on the results with year 2025, the annual N and P excretion of one adult ewe were 9.09 and 1.21 kg, respectively. Similar excretions for nine-month-old lamb raised for slaughter were 10.2 and 1.37 kg (when estimated for a whole year), respectively.
Keywords: faeces; goat; nitrogen; output; phosphorus; potassium; sheep; retention; manure; urine